Cancer-related cognitive impairment is associated with perturbations in inflammatory pathways. (December 2021) - Oppegaard, Kate; Harris, Carolyn S.; Shin, Joosun; Paul, Steven M.; Cooper, Bruce A.; Chan, Alexandre; Anguera, Joaquin A.; Levine, Jon; Conley, Yvette; Hammer, Marilyn; Miaskowski, Christine A.; Chan, Raymond J.; et al.
Highlights: Cancer-related cognitive impairment is a common clinical problem for patients. Clinical studies focused on cognition and gene expression in cancer are lacking. First study showing inflammatory pathways associated with cognition in cancer. Findings have potential to identify targets for therapeutics to improve cognition. Abstract: Cancer-related cognitive impairment (CRCI) is a significant problem for patients receiving chemotherapy. While a growing amount of pre-clinical and clinical evidence suggests that inflammatory mechanisms underlie CRCI, no clinical studies have evaluated for associations between CRCI and changes in gene expression. Therefore, the purpose of this study was to evaluate for differentially expressed genes and perturbed inflammatory pathways across two independent samples of patients with cancer who did and did not report CRCI. The Attentional Function Index (AFI) was the self-report measure used to assess CRCI. AFI scores of <5 and of >7.5 indicate low versus high levels of cognitive function, respectively. Of the 185 patients in Sample 1, 49.2% had an AFI score of <5 and 50.8% had an AFI score of >7.5. Of the 158 patients in Sample 2, 50.6% had an AFI score of <5 and 49.4% had an AFI score of >7.5. Data from 182 patients in Sample 1 were analyzed using RNA-seq. Data from 158 patients in Sample 2 were analyzed using microarray. Twelve KEGG signaling pathways were significantly perturbed between the AFI groups, five of which were signaling pathways related to inflammatory mechanisms (e.g., cytokine-cytokine receptor interaction, tumor necrosis factor signaling). This study is the first to describe perturbations in inflammatory pathways associated with CRCI. Findings highlight the role of cytokines both in terms of cytokine-specific pathways, as well as pathways involved in cytokine production and cytokine activation. These findings have the potential to identify new targets for therapeutics and lead to the development of interventions to improve cognition in patients with cancer.